Status Pengadilan Rakyat dalam Menyelesaikan Sengketa Tanah di Masyarakat Dago Elos - Wahyu, Fajar Ardiansah; Tamam, Mundzir; Musthofa, Ahmad Misbakh Zainul (Fakultas Hukum, Universitas Muslim Indonesia, 2024)
This study aims to analyze the status of the People’s Tribunal within the context of land dispute resolution in the Dago Elos community. This study uses a normative legal research method. The collected legal material is then qualitatively analyzed to describe the problem and answer the study objectives. The results show that despite lacking legally binding power, the People’s Tribunal plays a crucial role in fighting for justice and giving a voice to communities who feel their rights have been neglected by the formal judicial system. In the context of the Dago Elos land dispute, the People’s Tribunal serves as a platform for the community to articulate their dissatisfaction with court decisions perceived as unjust, and to fight for recognition of their rights to land and natural resources. The People’s Tribunal also symbolizes resistance against the legacy of colonialism and encourages more responsive legal reforms. Therefore, it is recommended that law enforcement agencies consider the People’s Tribunal’s verdict as valuable input in the law enforcement process, especially in cases involving structural injustice and human rights violations. The government needs to be more responsive to the aspirations of the community and strive for agrarian legal reforms that are more just, by recognizing and protecting the rights of local communities to land and natural resources. The community is advised to continue to strengthen the role of the People’s Tribunal as an alternative means of dispute resolution and upholding justice. In addition, the community is expected to participate in the decision-making process and oversee public policies related to the management of land and natural resources to ensure that these policies benefit the wider community and are sustainable.